Advertising in Digital Games: A Bibliometric Review. Issue 3 (2nd September 2019) - Yoon, Gunwoo
Abstract: Over the past decade, persuasive games (advergaming) and advertising in games (in-game advertising [IGA]) have been two types of engaging technology for promoting brands. This study examines how research on advertising within digital gaming has developed and evolved. The authors compile bibliometric data using the Web of Science, create a citation-based knowledge map, and explore the current state of research on advertising in digital games. Specifically, we employ bibliographic coupling and co-citation analysis methods and visually illustrate bibliometric networks. We discuss the topical relations and themes of advergaming and IGA research and further provide a robust road map for future research.